Example searcher: web development for spatial query via examples - Yew, Jun Xuan (Nanyang Technological University, 2022)
Location searches in spatial services such as online maps nowadays are usually based on traditional methods of criteria filtering. Due to its algorithmic design, this method only searches for one target location per query, ignoring the relation among multiple objects. In large-scale tasks, it is particularly inconvenient as users are required to specify each criterion. The concept of spatial search via examples has been introduced to address this problem, where an example of the search intent, a list of objects, is used for querying. The query will then return a list of results containing objects with similar properties as the input example. The project's objective is to develop a web application that implements an algorithm from the research paper based on the concept.